2015
DOI: 10.1016/j.bbi.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

IgG dynamics of dietary antigens point to cerebrospinal fluid barrier or flow dysfunction in first-episode schizophrenia

Abstract: Schizophrenia is a complex brain disorder that may be accompanied by idiopathic inflammation. Classic central nervous system (CNS) inflammatory disorders such as viral encephalitis or multiple sclerosis can be characterized by incongruent serum and cerebrospinal fluid (CSF) IgG due in part to localized intrathecal synthesis of antibodies. The dietary antigens, wheat gluten and bovine milk casein, can induce a humoral immune response in susceptible individuals with schizophrenia, but the correlation between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 123 publications
(156 reference statements)
2
41
0
2
Order By: Relevance
“…Studies of cerebrospinal fluid can lend some insight regarding how exogenous or gut-produced factors might gain proximity to the brain in schizophrenia [80, 89-91, 18, 56]. Toward this end, we found that antibodies directed against food antigens in the CSF are highly correlated with serum levels in samples from antipsychotic-naïve people with schizophrenia, a pattern not found in control individuals [18]. These data in conjunction with measurements of relative serum to CSF albumin and total IgG support the possibility of either an anatomical barrier abnormality or reduced CSF flow associated with schizophrenia [89,92].…”
Section: Epithelial and Endothelial Barrier Integritiesmentioning
confidence: 55%
See 2 more Smart Citations
“…Studies of cerebrospinal fluid can lend some insight regarding how exogenous or gut-produced factors might gain proximity to the brain in schizophrenia [80, 89-91, 18, 56]. Toward this end, we found that antibodies directed against food antigens in the CSF are highly correlated with serum levels in samples from antipsychotic-naïve people with schizophrenia, a pattern not found in control individuals [18]. These data in conjunction with measurements of relative serum to CSF albumin and total IgG support the possibility of either an anatomical barrier abnormality or reduced CSF flow associated with schizophrenia [89,92].…”
Section: Epithelial and Endothelial Barrier Integritiesmentioning
confidence: 55%
“…Further propagating this connection are the technological advances that have fueled the burgeoning field of microbiome research. In a series of research reports, we have united conceptually and experimentally a number of risk factors for the development of schizophrenia through a common origin in the gut [13][14][15][16][17][18]. The disease-associated interaction of such biological variables as humoral immunity to food antigens, intestinal inflammation, exposure to the parasite Toxoplasma gondii, endothelial barrier defects and microbial dysbiosis is consistent with a physiological model whereby gut-based processes can create a systemic state of immune dysregulation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, when blood-brain barrier is damaged, exorphins can pass from the intestinal lumen into the bloodstream (where they stimulate the immune system), and then pass into the CSF. It has been shown that in patients with schizophrenia, the higher the level of anti-gluten antibodies was detected in blood, the higher level of them was determined in the CSF [104]. This relationship suggests that in patients the spread of antibodies occurs on a larger scale than in healthy subjects, indicating some subtle, transient disorders of bloodbrain barrier.…”
Section: Exorphinsmentioning
confidence: 87%
“…Jednkaże, gdy bariera krew-mózg jest uszkodzona, egzorfiny mogą przedostawać się ze światła jelit do krwioobiegu (gdzie pobudzają układ immunologiczny), a następnie do CSF. Wykazano, że u chorych na schizofrenię, im wyższy poziom przeciwciał przeciwglutenowych wykrywano we krwi, tym wyższy ich poziom oznaczano w CSF [104]. Ta zależność sugeruje, że u osób chorych rozprzestrzenienie się przeciwciał zachodzi na szerszą skalę niż u osób zdrowych, co wskazuje na pewne subtelne, przemijające zaburzenia bariery krew-mózg.…”
Section: Egzorfinyunclassified